Successful late repair of popliteal artery rupture with compartment syndrome - Supomo Supomo (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Fatal Complications and high amputation rate were reported in popliteal artery rupture cases. Diagnosis delay and revascularization failure within 6 hour of Golden Period are related to amputation and death, even when specialist intervention is available. We report a patient with popliteal artery rupture and compartment syndrome, which was successfully underwent artery repair surgery after 42 hours of delayed revascularization. This case illustrates that delayed revascularization might produce an acceptable outcome in a particular circumstance.